Application of the Contextual Teaching and Learning Model Using Animated Power Point Media on Student Motivation and Learning Outcomes in Class XI High School Reaction Rate Material - Putri Jasrina; Rudi Munzirwan Siregar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research aims to test whether there is a difference in the learning outcomes of students who use the Contextual Teaching And Learning Model with the Doratoon Animation Powerpoint with the learning outcomes of students who use the Contextual Teaching And Learning Model with the Powtoon Animation Powerpoint on the Reaction Rate learning material, and to assess whether learning motivation students who use the Contextual Teaching And Learning Model with Doratoon Animation power points compared to the learning motivation of students who use the Contextual Teaching And Learning Model with Powtoon Animation power points on Reaction Rate learning materials and aims to find out whether there is interaction between models and media on students' final motivation in determining student learning outcomes in reaction rate learning material in class XI Science at SMA Negeri 1 Binjai - Langkat. The samples used were two classes selected by random sampling and classes XI IPA 1 and XI IPA 3 were selected. Hypothesis testing was carried out in two ways, namely the paired t test and the one way anova test. In the hypothesis test, the value of learning outcomes obtained a sig value of 0.001 < α= 0.05 so that H0 was rejected and Ha was accepted, so it was proven that learning outcomes were higher in classes that used the contextual teaching and learning model with Doratoon animated power point media. In terms of motivation, a significance value of 0.049 is produced, which is smaller than α= 0.05, so Ha is accepted and H0 is rejected, which shows that learning motivation is higher in classes taught using the contextual teaching and learning model with Doratoon animated power point media. In the interaction test, a sig.nificance value of 0.004 was obtained, which indicates a value < of α= 0.05 so that Ha is accepted and H0 is rejected, so there is an interaction between the model and the media on students' final motivation in the reaction rate material.